Sir C.P. Ramaswami Aiyar, a biography - Sundararajan, Saroja (Allied Publishers, 2002)
On the life and work of Sir Chetpat Pattabhirama Ramaswami Aiyar, 1879-1966, political activist, socialist, and educationist from Kerala and his role in erstwhile Travancore state and Madras Presidency.